2015
DOI: 10.1111/dme.12716
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and incidence of diabetes mellitus: a nationwide population‐based pharmaco‐epidemiological study in Sweden

Abstract: The prevalence of pharmacologically treated diabetes increased moderately during 8 years of follow-up, while the incidence decreased modestly. This is in contrast to the results reported by most other studies. The total prevalence of diabetes (both pharmacologically and non-pharmacologically treated) in Sweden is relatively low, from a global viewpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 27 publications
6
62
2
3
Order By: Relevance
“…4 The observed increase in physical activity may contribute to explaining why the rate of diabetes did not increase despite the increase in obesity. This finding is consistent with the observation in a Swedish registry study by Jansson et al, 19 who found the prevalence of pharmacologically treated diabetes to increase moderately during 2005-2013, whereas the incidence decreased modestly. Nevertheless, it should be noted that the prevalence of diabetes and obesity was much lower than that reported in in EUROSPIRE, a large European survey of patients diagnosed with CHD.…”
Section: Discussionsupporting
confidence: 92%
“…4 The observed increase in physical activity may contribute to explaining why the rate of diabetes did not increase despite the increase in obesity. This finding is consistent with the observation in a Swedish registry study by Jansson et al, 19 who found the prevalence of pharmacologically treated diabetes to increase moderately during 2005-2013, whereas the incidence decreased modestly. Nevertheless, it should be noted that the prevalence of diabetes and obesity was much lower than that reported in in EUROSPIRE, a large European survey of patients diagnosed with CHD.…”
Section: Discussionsupporting
confidence: 92%
“…A recent report from Sweden has also reported increasing diabetes prevalence, although at somewhat different rates from those described here. Jansson et al analysed the prevalence of pharmacologically treated diabetes (both type 1 and type 2 combined) during 2005 to 2013 and found on average a 27% higher prevalence and 10% higher incidence than our results showed [8]. A possible explanation for this discrepancy is that in contrast to Jansson et al, who used the PDR only, we used information from several nationwide data sources (the PDR, the Cause of Death Register and the National Patient Register) to assess diabetes diagnosis and censor patients with type 2 diabetes; this probably resulted in more accurate estimates of prevalence and incidence.…”
Section: Discussioncontrasting
confidence: 72%
“…There have been several national reports on diabetes prevalence and incidence, with different findings. Some describe an increased prevalence of diabetes [8,[12][13][14][15][16][17]; the majority report a stable incidence [12,13,15,16,18], some an increasing incidence [19,20] and one a decreasing incidence [8]. Explanations for these discrepant findings could be related to the decade in which the studies were performed, the definitions applied, the type of register used and the ethnic composition of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the international diabetes federation (IDF), it is estimated that 382 million people worldwide have diabetes (2)(3)(4). Furthermore, umbilical cord and Wharton's jelly (the vessels out of the umbilical cord) are better sources for Mesenchymal stem cells (MSCs), since they are globally accessible tissues and their gathering does not lead to any ethical harm, as they are ordinarily disposed as human waste (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%